1982
DOI: 10.1136/gut.23.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal permeability in coeliac disease: the response to gluten withdrawal and single-dose gluten challenge.

Abstract: SUMMARY Intestinal permeability has been studied in 21 patients with coeliac disease in relapse and after gluten withdrawal using an oral test of intestinal permeability based on the simultaneous oral administration of two probe molecules. The increased absorption of the larger molecule (cellobiose) and the decreased absorption of the smaller (mannitol) found in untreated coeliac disease both returned to normal within five months of starting treatment, the abnormality in cellobiose absorption correcting more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(51 citation statements)
references
References 28 publications
1
50
0
Order By: Relevance
“…113 More precise in vitro investigations revealed that although strict gluten withdrawal restored intestinal histology, a subjacent defect in mucosal permeability, measured by cellobiose/mannitol ratio, was transiently induced by short exposure to gluten, suggesting that increased intestinal permeability in celiac disease could be a primary defect. 135 Recently, this defect in intestinal permeability has been related to altered expression of TJ genes related to permeability, polarity, and cell proliferation in active celiac disease, 136 partly through the activation of the zonulin pathway in a MyD88-dependent fashion. 137,138 Again, the majority of genes returned to normal after 2 years of gluten eviction with the exception of PPP2R3A, possibly indicating a constitutive defect in these patients.…”
Section: Clinical Consequences Of Stress/ Corticotropin-releasing Facmentioning
confidence: 99%
“…113 More precise in vitro investigations revealed that although strict gluten withdrawal restored intestinal histology, a subjacent defect in mucosal permeability, measured by cellobiose/mannitol ratio, was transiently induced by short exposure to gluten, suggesting that increased intestinal permeability in celiac disease could be a primary defect. 135 Recently, this defect in intestinal permeability has been related to altered expression of TJ genes related to permeability, polarity, and cell proliferation in active celiac disease, 136 partly through the activation of the zonulin pathway in a MyD88-dependent fashion. 137,138 Again, the majority of genes returned to normal after 2 years of gluten eviction with the exception of PPP2R3A, possibly indicating a constitutive defect in these patients.…”
Section: Clinical Consequences Of Stress/ Corticotropin-releasing Facmentioning
confidence: 99%
“…These cells play a pivotal role in the maintenance of immune tolerance by down-regulating the immune response to foreign antigens when they gain access beyond the intestinal mucosal barrier (6). Recent studies in humans and in animal models have linked the presence of increased intestinal permeability to the occurrence of autoimmune diseases (8)(9)(10)(11)(12)(13). However, a causative role for the loss of the intestinal barrier function has not been definitively established.…”
mentioning
confidence: 99%
“…Here an ultrafiltration method followed by electrospray ionization (ESI) liquid chromatography-tandem mass spectrometry (LC-MS/MS) is used to determine if GEs can be detected in blood samples from subjects with compromised intestinal lining. Subjects with gluten-induced enteropathy (Celiac Disease, CD) were chosen as model subjects, because CD is well-known to result in increased intestinal permeability to macromolecules [6][7][8], and is frequently associated with mental disorders [9][10][11].…”
Section: Introductionmentioning
confidence: 99%